Tumor suppressor protein VHL inhibits Hedgehog–Gli activation through suppression of Gli1 nuclear localization. Issue 7 (8th February 2013) - Cho, Hyun Kook; Kim, So Young; Kim, Kook Hwan; Kim, Hyeong Hoe; Cheong, JaeHun
Abstract : VHL physically interacts with GLI1 by pull down (View interaction) Abstract : ► Tumor suppressor protein VHL decreases the expression of Hedgehog–Gli1 gene. ► VHL represses Gli1‐mediated Hedgehog target gene expression. ► VHL interacts directly with Gli1 protein. ► VHL co‐localizes with Gli1 in the cytoplasm and disturbs Gli1 nuclear localization. ► These results suggest that VHL may act as a tumor suppressor in some Hedgehog‐related cancers.